2010
DOI: 10.1021/jp108544v
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical Studies of trans-Bis(phenylethynyldiisopropylamidinato)bis(acetato)dimetal Complexes Involving MM Quadruple Bonds Where M = Mo or W

Abstract: The title compounds trans-M(2)(O(2)CMe)(2)[C((i)PrN)(2)C≡C-Ph](2), I (M = Mo) and II (M = W), show electronic absorptions in the visible region of the spectrum assignable to (1)MLCT [M(2)δ to phenylethynylamidinate π*]. These compounds show dual emission from S(1) and T(1) states. For both I and II, S(1) is (1)MLCT, but for I the T(1) state is shown to be MMδδ* while for II T(1) is (3)MLCT. The lifetimes of the S(1) and T(1) states have been determined by femtosecond and nanosecond transient absorption spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…However for II, our interpretation of the solvent dependence is that the initial absorption occurs without a significant change in dipole moment whereas that associated with the emission from the S 1 states is significant (14). Because the ground state molecules are symmetrical (D 2h ) and have a center of inversion, the Franck-Condon absorption conserves the point group symmetry to place the excited electron (14). The vibronic spacing together with the lack of solvent dependence in the T 1 state emission for II is consistent with the assignment of this state as the 3 MoMoδδ Ã state.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…However for II, our interpretation of the solvent dependence is that the initial absorption occurs without a significant change in dipole moment whereas that associated with the emission from the S 1 states is significant (14). Because the ground state molecules are symmetrical (D 2h ) and have a center of inversion, the Franck-Condon absorption conserves the point group symmetry to place the excited electron (14). The vibronic spacing together with the lack of solvent dependence in the T 1 state emission for II is consistent with the assignment of this state as the 3 MoMoδδ Ã state.…”
Section: Resultsmentioning
confidence: 72%
“…The more limited range of solubilities of compounds I and I 0 made the solvent dependent study less clear. However for II, our interpretation of the solvent dependence is that the initial absorption occurs without a significant change in dipole moment whereas that associated with the emission from the S 1 states is significant (14). Because the ground state molecules are symmetrical (D 2h ) and have a center of inversion, the Franck-Condon absorption conserves the point group symmetry to place the excited electron (14).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…16,17 Investigations by Chisholm and coworkers on the photoexcited states of trans-[M 2 (TiPB) 2 (O 2 CR) 2 ] (R = 2-thiophene 18,19 or C 6 H 4 -4-CN; TiPB = 2,4,6-triisopropylbenzoate) 20 show emission from T 1 states that are about the dimetal core also makes MM multiply bonded paddlewheel compounds good candidates for incorporation into materials with potentially interesting optoelectronic properties. [21][22][23][24][25][26][27] This was highlighted in a detailed study by Zhou and co-workers which demonstrated that the shape and size of molecular architectures formed using dicarboxylate ligands to bridge Mo 2 4+ units can be controlled by tuning the bridging angle and size of the bridging dicarboxylate ligand.…”
Section: Introductionmentioning
confidence: 99%
“…25 Several recent papers have studied the different cases of dymolibdenum compounds with special ligands. [26][27][28][29][30][31][32][33][34][35] A complete revision of these is out of the scope of this study. Some of them use DFT as a tool for understanding the structure of these compounds [30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%